The effect of foreign debt on the economic growth - Kurniasih, Erni Panca (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study examines the effect of foreign debt on the economic growth. Using a time series Indonesian data over 1981 - 2017, we employ the Error Correction Model based on the debt overhang theory. Foreign debt was found to produce negative and significant effect on the economic growth both in the short- and long-run. The paper further found that Foreign Direct Investment (FDI) improves the economic growth. Foreign debt that continues to increase drastically in the long-run could slow down the economic growth which may indicate the economy experiencing a debt overhang. It is thus imperative for the government to ensure the debt ratio remain below a certain threshold. Further, foreign debt should be prioritized to develop infrastructure with a broad multiplier effect and the FDI likewise prioritized for labor-intensive sectors.